Understanding sprint-cycling performance: The integration of muscle power, resistance, and modeling - Martin, J. C.; Davidson, C. J.; Pardyjak, E. R. (International Journal of Sports Physiology and Performance, 2007)
Sprint-cycling performance is paramount to competitive success in over half the world-championship and Olympic races in the sport of cycling. This review examines the current knowledge behind the interaction of propulsive and resistive forces that determine sprint performance. Because of recent innovation in field power-measuring devices, actual data from both elite track- and road-cycling sprint performances provide additional insight into key performance determinants and allow for the construction of complex models of sprint-cycling performance suitable for forward integration. Modeling of various strategic scenarios using a variety of field and laboratory data can highlight the relative value for certain tactically driven choices during competition.